Bagaimana bertutur Bahasa Arab seperti penutur jati (How to speak Arabic like native speakers) - Abdullah, Mohd Ikhwan (2019)
Arabic Language is just like other languages. If one wants to master a language he or she must think the way the language speakers speak. In this seminar, I shared some tips on how to think and speak Arabic Language like Arabs.